Reflections to construct inter-institutional dialogues. The experience of the Rafaela Social Advisory Council (Santa Fe, Argentina). Path dependences and present - Delbon, Samuel (Universidad Nacional del Litoral, 2022)
In this article we seek to generate reflections on the territorial governance process of the City of Rafaela (Santa Fe, Argentina), exposing inter-institutional dialogues and recovering the voice of actors to analyze what happens in this context marked by the COVID-19 pandemic. Specifically, we return to the experience of the Rafaela Social Advisory Council as a space for dialogue between various actors. Likewise, we address our gaze on how the dialogue processes developed in the current context, even in physical distance and with the complexity and uncertainty generated by this year and a half of pandemic.